Incidence of Methicillin Resistant Staphylococcus Aureus (MRSA) Among Patients Necessitating Reconstructive Surgery - Sami Atiq, Eesha Tehreem, Arslan Murtaza, Fahd Karamat Baig, Usama Atiq, Rameen Rafique (Pakistan Journal of Medical & Health Sciences, 2022)
Purpose: Staphylococcus aureus is an important nosocomial pathogen and the progression of methicillin resistance stances a most important threat for its control. The current study was directed to govern the MRSA prevalence and its susceptibility to various antibiotics given for anti-staphylococcal strains in OPD treated patients. Study design: Prospective descriptive study. Place and duration: This study was conducted in the East Surgical Ward of Mayo Hospital, Lahore for two-year duration from January 2020 to December 2021. Methods: A total of 200 patients with septic wounds of both sexes were encompassed in the study. Swabs were taken from wounds which were infected and Stuart’s medium was used to transport them. The samples were grown onto MacConkey agar, nutrient agar and blood agar and for 24 hours; incubated at 37 ° C. All MRSA isolates were biochemically and morphologically identified using standard procedures of laboratory by processing clinical specimens submitted to a microbiology laboratory. All isolates were tested for patterns of resistance and sensitivity. Results: A total of 200 patients were included, 115 (57.5%) were men and 85 (42.5%) were women with 27.3 years of mean age and age range from 15-70 years. The incidence of positive cases confirmed by culture was 118 (59%) and the MRSA incidence was 78 (39%). Of the 78 cases of MRSA, 50 (64.10%) are men and 28 (35.90%) are women. The incidence of other microorganisms was 40 (33.8%). MRSA was 100% sensitive to vancomycin, teicoplanin and linezolid. Of these, 24.4% were sensitive to cotrimoxazole, 47.4% were sensitive to fucidic acid and 28.2% were sensitive tetracycline antibiotics. Cultured MRSAs were resistant 100% to main antibiotic groups including penicillin, macrolides, cephalosporins, fluoroquinolones, meropenem, imipenem, gentamicin, and tazobactum/ pipracillin. Of all 78 MRSA patients, > 50% were from general surgery and orthopaedics departments, and the remainder from other related specialties, such as Gynecology, pediatric surgery, maxillofacial surgery, neurosurgery and otolaryngology. Of 78 patients with MRSA, 70 (89.7%) were hospitalized with a history of hospitalization, and 60 (76.9%) were hospitalized for >1-week. The organism was institute to be hundred percent resistant to the generally directed antibiotics. Conclusions: The incidence of MRSA is increasing. The organism spreads readily in a hospital setting, causing morbidity, mortality and higher costs. Special infection control actions and precautions should be taken to stop and prevent the MRSA spreading.